Comparing chains versus independent hotels based on international sales: an exploratory study - Ribaudo, Giorgio; Moccia, Salvatore; Orero-Blat, María; Palacios-Marqués, Daniel (Economic Research-Ekonomska Istrazivanja, 2020)
The globalization of tourism has recently increased the importance of foreign demand for most European destinations. Hotel chains have been long investigated from several perspectives. However, no research has verified the alleged ability of chains to attract foreign demand, while this information is highly sought after by hotel investors and owners when evaluating affiliation opportunities. The present study covers Italy. It is based on a survey of 148 branded hotels for 21 destinations and 22 brands. Adopting a new metric to compare the ability of hotels to sell abroad (Foreign market Per Available Room; FmPAR), it has been found that chain-affiliated hotels perform better than independent hotels in attracting foreign demand. This is particularly true for international chains compared to domestic ones. On the other hand, the effect is stronger in three-star hotels than in four and five-star ones, in destinations where chain penetration is low.
Keywords: brand strategy; Hotel chains; international demand; sales performance; Scopus; JCR